Fundamental Concepts of Work Ethics in Islamic Perspective and Its Implementation in Islamic Bank Marketing - Aravik, Havis; Hamzani, Achmad Irwan; Khasanah, Nur; Tohir, Ahmad (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2024)
This article wants to discuss the basic concepts of work ethics in Islamic Perspective and its Implementation in Islamic Bank Marketing. This is important to do because ethics is one of the components that must exist in various activities including in the field of marketing in order to produce various benefits for various parties, and not harm other parties. The method used is a literature study. The data used in this research comes from library data, such as books, encyclopedias, dictionaries, journals, documents and other relevant data. The results of this research show that work ethics is something that is very important in work. Ethics guide, encourage and direct work attitudes and behaviour to values that are in line with religious teachings, legal and societal norms. Islamic bank marketing work ethics in principle aims to ensure the embedding of seeds of professionalism, sincerity, harmony and creating justice in public relations, thereby increasing dignity, and upholding human rights such as when carrying out promotions must use soft words, be polite and full of responsibility, be professional, transparent and the position of consumers or customers is placed as equal as partners. Being wise to competitors and the work culture created is different from conventional institutions.